Improving school attendance - Blyth, Eric; Milner, Judith, senior lecturer (Making the most of SIMS .net., 1999)
This book will be the first in several years concerned with non-attendance. Previously unpublished material in the book will provide a multi-disciplinary evaluation of practice at LEA, whole school and individual levels.